Maternal mental health and partner delivered massage: a pilot study. (30th September 2020) - Hall, H; Munk, N; Carr, B; Fogarty, S; Holton, S; Weller, C; Lauche, R
Abstract: Background: Mental health problems place a significant burden on the health system and are an important public health issue. Many pregnant women experience anxiety and depression, which can negatively impact health outcomes for both mother and baby. Partner-delivered massage may provide a cost effective and accessible approach to support the mental wellbeing of pregnant women. Methods: A feasibility randomised controlled trial was conducted to compare partner-delivered relaxation massage (intervention) with a self-directed stress management program (control), for pregnant women with mild anxiety. Women attended an initial workshop at 28-32 weeks gestation, followed by the completion of either the self-directed massage or stress management program. Qualitative feasibility and acceptability data (primary outcomes) were collected via online participant diaries and post-birth interviews. Anxiety, depression and stress symptoms (secondary outcomes) were assessed using the Depression and Anxiety Stress Scale (DASS-21). Results: 14 women/partner dyads attended the partner- delivered massage group and 13 women attended the self-directed stress management group. Participants from both groups reported the programs were feasible and acceptable. Mean scores on all DASS-21 subscales significantly decreased over time in both the intervention and the control group. Conclusions: The partner-delivered massage program was feasible and acceptable. Both programs decreased women's symptoms of anxiety, depression and stress, with no significant between-group differences identified. An adequately powered, experimental study is needed to determine the effectiveness of partner-delivered relaxation massage. Key messages: Many women experience anxiety and depression during pregnancy and this can have a negative impact on both mother and baby. Partner-delivered relaxation massage, at least once a week in the third trimester, may help reduce women's symptoms of anxiety, depression and stress.